Transformasi Pembelajaran di Masa Pandemi : Dari Tatap Muka ke Dunia Maya - Lisna Syahfitri; Cut Kumala Sari; Tarisa Sri Ramadhani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The COVID-19 pandemic has drastically changed the way people communicate, especially in the world of education. Learning that previously took place face-to-face has shifted to a virtual system in response to government policies regarding social distancing. This study aims to examine the culture of virtual communication during the COVID-19 pandemic using a literature study approach and secondary data analysis from various trusted sources, including national journals. The results of the study show that virtual communication has become an important part of the learning process during the pandemic. Various platforms such as Zoom Meetings, Google Classroom, and Google Meet are widely used by educators and students to support interaction and the effectiveness of the teaching and learning process. This study also highlights changes in communication patterns, challenges faced by users, and the importance of technological readiness and digital literacy in supporting effective virtual learning during a crisis such as a pandemic.